2005
DOI: 10.1016/j.otohns.2004.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis and biofilms

Abstract: This is the first documentation of biofilms in association with chronic rhinosinusitis. Further investigation is warranted, especially with control research subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
109
0
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 16 publications
2
109
0
9
Order By: Relevance
“…They defined the tower-shaped formations comprised of aggregates of matrix-encased bacteria as the morphological hallmark of biofilms. Ramadan et al [22] also reported evidence of biofilms in specimens obtained from all of five patients by SEM and transmission electron microscopy (TEM). The morphological criteria for biofilms by SEM are water channels, 3-D structure, and matrix-embedded spherical or elliptical bodies within the bacteria ranging from 0.05 to 5.0 lm.…”
Section: Discussionmentioning
confidence: 94%
“…They defined the tower-shaped formations comprised of aggregates of matrix-encased bacteria as the morphological hallmark of biofilms. Ramadan et al [22] also reported evidence of biofilms in specimens obtained from all of five patients by SEM and transmission electron microscopy (TEM). The morphological criteria for biofilms by SEM are water channels, 3-D structure, and matrix-embedded spherical or elliptical bodies within the bacteria ranging from 0.05 to 5.0 lm.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, several studies describe biofilms consisting of unidentified bacteria on the surfaces and crypts of adenoids removed from children being treated for COM, CRS, chronic adenotonsillitis, and OSA and within the tissue and crypts of inflamed tonsils from children with chronic tonsillitis (1,11,38,55), demonstrating that uncharacterized bacterial biofilms are present in other chronic URT infections. Biofilm infections are clinically significant because these three-dimensional (3D), adherent, organized communities of bacteria are far more recalcitrant to antibiotic therapy and killing by host phagocytic cells (27,30,35).…”
mentioning
confidence: 99%
“…In our case, the colonization was dominated by Mucor species, which do rarely form fungus balls (Table 1) and are mostly related to an acute fulminant invasive mycosis of the sinuses (Dhong 2000, Goodnight 1993, Henderson 1988, Pérez Fernández 2001, Ramadan 2006, and Saydam 1997 Dhong, Jung and Park (2000) refer to two cases of Mucor fungus balls but details could not be retrieved A fungus ball appears usually in one sinus, most frequently the maxillary, and is noninvasive. A rare case of an involvement of more than one sinus was presented by Chao (2004).…”
Section: Discussionmentioning
confidence: 72%
“…Mucor colonization of the sinuses is rare and usually occurs without predisposing factors in immunocompetent individuals in contrast to mucormycosis which is the second most frequent mycosis caused by moulds in immunocompromised patients (Sugar 1992). In these patients, the species are mostly related to an acute fulminant invasive mycosis of the sinuses (Dhong 2000, Henderson 1988, and Ramadan 2006. Gamba et al (1986) point out that paranasal sinus involvement can commence early in the course of the disease with radiological signs of mucosal thickening without formation of air-fluid level and rarely with bone erosion.…”
Section: Introductionmentioning
confidence: 99%